Електрохімічне формування молібденвмісних анодних оксидних покриттів на сталі 08Х18Н10 - Штефан, Вікторія Володимирівна; Кануннікова, Надія Олександрівна (Київський національний університет технологій та дизайну, 2019)
The kinetics of the anodic formation of oxide layers on steel in the potentiodynamic mode with a potential sweep rate of 2 mV·с-1 in acidic sulfate electrolytes was studied using the linear voltammetry method. It has been established that an increase in the concentration of molybdenum oxoanions leads to an increase in anodic currents and an expansion of the active dissolution region, to a shift of the stationary potential to an electropositive region, which indicates that oxoanions passivated the steel surface. Studies of the morphology and structures of the obtained coatings revealed that an increase in the concentration of molybdenum oxoanions leads to a decrease in the size of the globules, and at a certain concentration the association of the globules is observed.
Еlectrochemical formation of molybdenum containing anode oxide coatings on AISI 304 steel
Keywords: корозійна стійкість; аустенітні хромонікелеві сталі; механічний знос; анодування; оксоаніони; stainless steel; voltammetry; anodic oxide coatings; molybdenum; morphology; corrosion; impedance